How COVID-19 reshapes new world order political economy perspective - Li, Sheng (Springer, 2022)
This timely book explores economic, political, social, and cultural impacts of the COVID-19. It aims to reveal a future world shaped by the worldwide pandemic. The main content of this book is divided into 5 parts: the pandemic's short sketch of the pandemic through 2020, the acceleration of the global power transition: from East to West, comparison between authoritarian and democratic in the pandemic era, global international organizations under the COVID-19 influence, and regional international organizations under the COVID-19 influence. In addition, this book also analyzes the impacts from two aspects: the changes of the world order and the repercussions for international organizations and globalization.
Keywords: Pandemie; Internationale Politik; COVID-19; Internationale Organisation; COVID-19 Pandemic, 2020- / Social aspects; COVID-19 Pandemic, 2020- / Political aspects; Social aspects